Reasons for the bubbling chemical effect and differentiation of ions in the formation of marine aerosols (physico-chemical analysis) - Kuschnir, S.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
It is shown that the main cause of bubbling chemical effects in solutions of NaCl is structural changes in the gas/water interface, which lead to a strong increase in the structural water temperature and increase its acidity due to the increase in the concentration of dimeric associates (H2O)2. The increase in the structural temperature in the bulk water is observed in the turbulent regime of the mechanical mixing of a solution and leads to a strong decrease in the solubility of oxygen. Differentiation of ions in the formation of aerosols can be explained by the concentration of stable neutral ion pairs in the interfaces in the formation of gas bubbles.